The Legal Pluralism in Law Education in Indonesia - Rahmat Bin Mohamad; I Wayan Rideng (Fakultas Hukum, Universitas Warmadewa, 2021)
This paper aims to analyze the practice of legal pluralism in Indonesia. A decentralized approach policy enables the growth and the development of various legal systems. By the prevailing of the pluralism of legal system apparently also raises the problem in its application. But in reality, various living legal systems can co-exist. The method applied is based on normative study, with qualitative approach. The result shows that the legal system that pluralism is very influential on the development of education, including law education. Law education in Indonesia is also influenced by the history of Indonesia. The new pattern of law education in Indonesia can only lead people to an obedience and legal compliance. Legal education is not an independent thing, but it is related to social issues. So it has implications for the many violations of law and the emergence of criminal acts. This shows the level of legal awareness of the community is still low. Then it will also affect the legal culture and law enforcement in a country.